Media Sosial sebagai Pengawasan Publik: Implikasi terhadap Penegakan Hukum dan Keadilan Sosial - Novemyanto, Alfin Dwi (CONSTITUO : Jurnal Riset Hukum Kenegaraan dan Politik, 2025)
The "No Viral No Justice" phenomenon indicates society's dependence on the pressure created by the virality of information on social media as a means to encourage law enforcement. In many cases, especially those involving violence, discrimination, or injustice against vulnerable groups, the spread of information via social media often becomes a primary motivator for law enforcement to take quicker action. This problem formulation is related to social media as a catalyst for social change in public oversight and the implications of social media in social engineering regarding law enforcement and social justice. This study uses a normative legal approach, case study data collection techniques, and data obtained from literature relevant to the research topic. The data presentation technique used is descriptive and thematic analysis. The use of social media for law enforcement oversight is an example of Social Engineering, where public pressure via social media aims to guide law enforcement agencies to expedite judicial processes and act more justly. The "No Viral No Justice" phenomenon demonstrates how social media can create urgent social pressure to ensure that justice is achieved, even when formal legal procedures take longer. In this context, social media acts as part of the Social Engineering mechanism, influencing the law to be more responsive to social justice demands. The implications of social media on law enforcement and social justice may include increased transparency and accountability, as well as impacts on social justice. With public pressure via social media, the law enforcement process can become faster, more transparent, responsive, and prevent abuse of power.